DAMPAK PANDEMI COVID-19 TERHADAP KETERSERAPAN LULUSAN SMK KE DUNIA KERJA - Sudiyono; Relisa (Jurnal Penelitian Kebijakan Pendidikan, 2022)
This study aims to examine the impact of the COVID-19 pandemic on the employment of Sekolah Menengah Kejuruan (SMK), Indonesia’s formal vocational school at the secondary level graduates. The variables studied related to the employment of SMK graduates were the number of SMK graduates, the factors that affect how quickly graduates get jobs, and the activities carried out by SMK graduates before getting a job. This research used a mixed method, while data analysis used primary and secondary data. Data were collected through literature reviews, online surveys, and focus group discussions. To find out further about the impact of the pandemic, an online survey was conducted on the year 2020 SMK graduates majoring in technology and engineering and also tourism program. The results showed that there was a decline in the employment rate of SMK graduates from all programs, when compared to the pre-pandemic period in 2019. This decline reached 3.19% in 2020 and 0.77% in 2021. Factors that influenced the employment of SMK graduates were skills and competency, motivation, and the availability of job vacancies. Activities carried out by SMK graduates before getting a job were seeking job information, learning to be self-employed, and attending courses/training.